Assessment of genetic variation for pathogen-specific mastitis resistance in Valle del Belice dairy sheep. Issue 1 (December 2016) - Tolone, Marco; Larrondo, Cristian; Yáñez, José; Newman, Scott; Sardina, Maria; Portolano, Baldassare
Abstract Background Mastitis resistance is a complex and multifactorial trait, and its expression depends on both genetic and environmental factors, including infection pressure. The objective of this research was to determine the genetic basis of mastitis resistance to specific pathogens using a repeatability threshold probit animal model. Results The most prevalent isolated pathogens were coagulase-negative staphylococci (CNS); 39 % of records and 77 % of the animals infected at least one time in the whole period of study. There was significant genetic variation only forStreptococci (STR). In addition, there was a positive genetic correlation between STR and all pathogens together (ALL) (0.36 ± 0.22), and CNS and ALL (0.92 ± 0.04). Conclusion The results of our study support the presence of significant genetic variation for mastitis caused byStreptococci and suggest the importance of discriminating between different pathogens causing mastitis due to the fact that they most likely influence different genetic traits. Low heritabilities for pathogen specific-mastitis resistance may be considered when including bacteriological status as a measure of mastitis presence to implement breeding strategies for improving udder health in dairy ewes.